THE CONCORDANCE OF BRIXIA AND RALE SCORES IN EVALUATION OF COVID-19 PNEUMONIA PATIENT USING RADIOGRAPHY IN INDONESIA REFERRAL HOSPITAL - Lina Choridah; Anita Ekowati; Nurhuda Hendra Setyawan; Bestari Ariningrum Setyawati; Naela Himayati Afifah; Anggraeni Ayu Rengganis (UPPM, Poltekkes Kemenkes Semarang, 2023)
The COVID-19 pandemic has put intense pressure on the healthcare systems. As the lung complication of COVID-19, pneumonia can be assessed by chest radiography which can be used to predict the severity of patient deterioration using Brixia and RALE scores. This research aims to assess the Radiologists' agreement on diagnosing pneumonia COVID-19 by RT-PCR in CXR using the Brixia and RALE score at Dr. Sardjito Central General Hospital from May 2020-January 2021. Two separate radiologists scored initial chest radiographs for RALE and Brixia independently. The analysis assessed included a descriptive analysis of demographic data, and Bland-Altman plots were used to visualize intra-observer agreement. A total of 332 samples were 162 men (48.8%) and 170 women (51.2%), with a mean age of 42.37. The ICC of Brixia score (0.855, CI:0.794-0.895) and RALE score (0.756, CI:0.662-0.812). Bland-Altman analysis revealed a bias of 5.08 ± 6.04 (95% limits   of agreement of -6.760 and 16.929) for Brixia and RALE scores and significantly correlated (r=0.886 (p0.05)). The average score of Brixia (6.29±4.430) and RALE (11.56±9.997) in men was higher than in women. The agreement of Radiologists in diagnosing pneumonia COVID-19 using Brixia and RALE scores with the Bland Altman curve was significant or reliable.